1980
DOI: 10.1002/pol.1980.170180206
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polyelectrolytes. I. Soluble polymers prepared from reaction of chloromethylated polystyrene with tris(2‐hydroxythyl)amine

Abstract: The reaction of chloromethylated polystyrene with tris(2‐hydroxyethyl)amine in N,N‐dimethylformamide is described for the conditions to prepare soluble reaction products. The groups of the quaternary ammonium salt, which appear in the first stage of the reaction, transpose to the amino‐ether groups. The reaction was followed by elementary analysis, IR and 1H‐NMR spectra, and viscosimetric measurements for nondialyzed and dialyzed samples. The presence of the tertiary amine groups on obtained polymers was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Dragen et al [18,19] reported the formation of soluble and cross-linked polymers by reacting chloromethylated polystyrene with tris-(2-hydroxyethyl) amine. Ferruti et al [6,7] aminated PVC using a concentrated aqueous solution of bis-(2-aminoethyl) amine.…”
Section: Resultsmentioning
confidence: 98%
“…Dragen et al [18,19] reported the formation of soluble and cross-linked polymers by reacting chloromethylated polystyrene with tris-(2-hydroxyethyl) amine. Ferruti et al [6,7] aminated PVC using a concentrated aqueous solution of bis-(2-aminoethyl) amine.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, oxidations and reductions find only limited use in post‐polymerization modification, with examples being the reduction of poly( N ‐acetylethyleneimines) yielding poly( N ‐alkylethyleneimines)48 or the oxidation of poly(vinyl alcohol) with NaOCl yielding poly(enol‐ketone) 49. Functionalized polystyrenes have been prepared by various substitution reactions, which include amination and quaternization of chloromethylated polystyrene,50–52 Friedel‐Crafts reactions on polystyrene,53–55 sulfonation of polystyrene,56 as well as the lithiation of polystyrene 57–61. Other examples include the chlorination of cross‐linked polystyrene‐divinylbenzene beads10 as well as the modification of halogenated or lithiated poly(meth)acrylates 11, 12…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Reaction of crosslinked amine function resin in dimethylformamide with excess 2‐chloroacetamide yielded a product with a chloride content of 2.5 mmol/g, corresponding to about 73.5% quaternization. However, quaternization of ethanol amines have been reported to rearrange to diethylamino ether moieties spontaneously 21…”
Section: Resultsmentioning
confidence: 99%